Sustainability Reporting in the Antwerp Port Ecosystem, Belgium: Understanding the Relationship Between Reporting on the Sustainable Development Goals and Integrated Thinking - Beyne, Jan; Visser, Wayne; Allam, Imane (Frontiers in Sustainability, 2021)
This paper is aimed at elucidating the interrelations between reporting on the Sustainable Development Goals (SDGs) and integrated thinking. A review of online information on sustainability by port community companies in Antwerp, Belgium was applied. The research made use of a database from Port Plus investigating 769 companies. The data were analyzed using a combination of descriptive and inferential analyses. The research shows that reporting on the SDGs and integrated thinking have reciprocal reinforcing relationships, where the SDGs are a good starting point for planning integrated strategies for sustainability. The article reinforces that using the SDGs in communication and reporting can help companies better and more holistically integrate their efforts for sustainability into their strategies and processes.